PENGELOLAAN DAYA TARIK WISATA PULAU KUMALA OLEH DINAS PARIWISATA KABUPATEN KUTAI KARTANEGARA - Bhatari Lolita Pratiwi (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
This research project is being studied at kutai kartanegara district by tourist attraction kumala island. The purpose of writing this essay is to identify and describe the management of tourism services in kumala district kutai kartandistrict and also to identify the obstacles -- obstacles which the tourism service deals with in kumala island tourist management in kab. Kutai Kartanegara. The focus of the study in this study is of attraction, ability, facilities and obstacles faced by the tourism service in the management of kumala island tourist attractions at kab. Kutai Kartanegara.The kind of research used is qualitative descriptive. Data collection techniques are done in literature and field research consisting of observations, interviews, and documentaries, whereas the informants who were taken purposive sampling and accidental sampling.Studies show that the tourism service has achieved management according to its duties and functions in managing the tourist attractions of island kumala, this is indicated by implementation of the 3 (3) indicators taken from its service one area of the tourism service that they are partly accomplishing, But they have constraints that are, in fact, the lack of budget that's keeping them in the sense that their management is somehow hampered and not maximum.